Supercritical fluid foaming : a novel route to polymeric allografts? - Purcell, Matthew S. (2014)
There is a growing need for synthetic bone graft materials, which is particularly apparent for procedures requiring impaction bone grafting (IBG), such as revision hip arthroplasty. Currently allograft bone is used that has limited supply and associated risks of transmission of infectious agents. Porous bioresorbable polymeric scaffolds can be created using supercritical carbon dioxide (scCO2). This thesis investigated the use of these scaffolds for impaction bone grafting procedures. Building on previous research within the literature poly(D,L-lactide) (PDLLA) and poly(D,L-lactide-co-glycolide) (PDLLGA) scaffolds of high molecular weight (100 kDa) were investigated for this use. Scaffolds were milled using a standard bone mill and impacted to create porous milled chips of bioresorbable scaffolds and impacted for mechanical shear testing and biocompatibilities. The impaction process used forces equivalent to those experienced during IBG. In vitro cell experiments were used to assess the proliferation and osteoblastic differentiation of mesenchymal stem cells (MSCs) on impacted scaffolds to identify the most promising scaffold compositions. These compositions included pure polymer and polymer:HA microparticle composites. Further experiments using animals (murine and ovine) were then used to investigate the in vivo performance of the scaffolds. A critical sized ovine femoral condyle defect established the osteoinductive and osteoconductive potentials of milled scCO2 foamed PDLLA + 10 wt.% hydroxyapatite (HA) microparticle scaffolds in vivo. The scale-up potential of scCO2 foaming of bioresorbable scaffolds was established using a 1 L vessel. Scaffolds scCO2 foamed using either a 60 ml autoclave or a 1 L vessel were characterised using scanning electron microscopy and micro computed tomography. Scaffolds from different batches were characterised and compared to ensure process repeatability was accounted for. The final chapter investigated differences in the osteoblastic differentiation of MSCs on PDLLA and PDLLGA scaffolds observed in experiments at the start of the study. Spincoated and dipcoated flat films of PDLLA, PDLLGA, and PDLLA:PDLLGA (50:50) were used for in vitro cell culture to remove the effect of morphological differences that affected scCO2 foamed scaffold experiments. Additionally, this chapter investigated the effect of the form of HA using HA nanoparticles andHA microparticles in scCO2 foamed PDLLA:HA composites for in vitro studies.